2017
DOI: 10.1002/jat.3561
|View full text |Cite
|
Sign up to set email alerts
|

Effects of triclosan on Japanese medaka (Oryzias latipes) during embryo development, early life stage and reproduction

Abstract: Triclosan has been shown to have endocrine-disrupting effects in aquatic organisms. In 2016, the US Food and Drug Administration banned the use of triclosan in consumer soaps. Before the ban, triclosan was reported at low concentrations in the aquatic environment, although the effect of triclosan on reproduction in teleost fish species is yet to be clarified. Here we investigated the effects of triclosan on embryo development and reproduction, and during the early life stage, in Japanese medaka (Oryzias latipe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 45 publications
1
14
0
Order By: Relevance
“…This study suggests that it is necessary to investigate not only the embryo stage (when various organs and tissue are formed) but also the influence after hatching (when all organs and biological functions are working normally), to evaluate accurately the influence of diclofenac. In addition, it has been previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Mu et al, ; Yang et al, ). Furthermore, we revealed that triclosan exposure also negatively affects with a particularly steep increase in mortality soon after hatching in O. latipes (Horie, Yamagishi, Takahashi, Shintaku, et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This study suggests that it is necessary to investigate not only the embryo stage (when various organs and tissue are formed) but also the influence after hatching (when all organs and biological functions are working normally), to evaluate accurately the influence of diclofenac. In addition, it has been previously demonstrated that the embryonic and larval stages of zebrafish have different sensitivities to toxic chemicals (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ; Mu et al, ; Yang et al, ). Furthermore, we revealed that triclosan exposure also negatively affects with a particularly steep increase in mortality soon after hatching in O. latipes (Horie, Yamagishi, Takahashi, Shintaku, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, toxicity testing using zebrafish embryos has been recommended from the point of view of animal welfare (EU, ). Ecotoxicological assays using zebrafish are increasingly used to clarify whether environmental chemicals induce abnormal embryogenesis because this effect is often induced at exposures lower than those are that cause lethal effects (Horie, Yamagishi, Koshio, et al, ; Horie, Yamagishi, Takahashi, et al, ). Indeed, there are reports that diclofenac induces abnormal embryogenesis in zebrafish (Chen et al, ; Horie, Yamagishi, Koshio, et al, ; Ribeiro et al, ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Earlier findings have indicated that the TCS is highly toxic to aquatic organisms. It was reported that TCS cause developmental anomalies with embryotoxicity and biochemical changes, bioaccumulation, endocrine disruption, and reproductive effects in Japanese medaka (Foran, Bennett, & Benson, 2000;Horie, Yamagishi, Takahashi, Iguchi, & Tatarazako, 2017;Ishibashi et al, 2004) and zebrafish (Falisse, Voisin, & Silvestre, 2017;Oliveira, Domingues, Grisolia, & Soares, 2009). In male medaka (Foran et al, 2000), triclosan has been shown to exhibit changes in fin length and sex ratios, suggesting that triclosan has a weak androgenic effect.…”
Section: Introductionmentioning
confidence: 99%
“…Due to the persistence and toxicity of TCC, its aquatic ecotoxicity has attracted wide attention [4]. In recent years, its toxic effects, such as inhibitory effects on growth and development, endocrine disruption, and reproductive toxicity, have caused great concerns [5][6][7][8][9][10][11]. Several studies provided evidence that TCC interferes with biological receptors in vitro, including a stably transfected aryl hydrocarbon receptor (AhR)-, androgen receptor (AR)-, or estrogen receptor (ER)responsive firefly luciferase reporter gene that responds to chemicals that can bind to and/or activate the respective receptor [12].…”
Section: Introductionmentioning
confidence: 99%